Brand Trust of a Listed Company by Investor Relations Activities: Research Results - Beata TARCZYDŁO (Communications of International Proceedings, 2021)
The article was motivated by the question about the role of online information platforms and investor relations (IR) activities carried out via such platforms in building brand trust in a listed company brand, how they are related to the current conditions of the COVID-19 pandemic and what results they bring. The study discusses the generalised results of the author’s own research of secondary sources with the use of published studies and available research reports on investor relations practices in Poland and across the world (from the years 2006-2021), analyses of online content from investor relations services and industry vortals (from the years 2019-2021), as well as participant observation, and a case study of several dozen listed companies (WIG30) from the period from January to April 2021. The discussion and qualitative research carried out confirmed that methodical investor relations activities for the listed company brand are an important management tool contributing to stakeholders’ trust. IR practices are certainly contingent in law, yet the COVID-19 pandemic and the competitive structure significantly contribute to the increasing role of the use of special IR services/platforms in the process of effective communication, strengthening relationships, cooperating with stakeholders in real time, taking into account perfecting the forms and manners of communication, which enables dialogue, creates value for all the entities involved, and ultimately translates into confidence in listed companies. The research also have shown that contemporary personified brands should be transparent by implementing adequate investor relations strategies, which directly translates into increased trust in these brands.
Keywords: listed company brand; building brand trust; investor relations activities and their results; results of research on listed companies’ IR practices.